"Hello, abattoir!": Becoming Through Slaughter in Miriam Toews’s A Complicated Kindness - Soper, Ella (Studies in Canadian Literature, 2011)
Drawing on the tradition of both the Bildungsroman and the Künstlerroman, Miriam Toews’s A Complicated Kindness (2004) presents animal slaughter as the central symbol of adolescent becoming. In her depiction of Happy Family Farms, the local chicken processing plant in East Village, Manitoba, Toews offers a rigorous critique of the ways in which the town resists its own cultural erasure by rebranding itself as a town open for business – in this case, factory farming. Because a career at the abattoir is one of the few vocational opportunities open to young people like conflicted Mennonite teenager Nomi Nickels, Toews builds narrative suspense by alluding to the job awaiting Nomi if she chooses to remain in East Village. True to the dynamic structure of the novel, Nomi defers this decision, thus rejecting the closure of having become for the more episodic process of becoming. In this way, Toews crafts an ironic commentary on the teleology of coming-of-age narratives.